Pengaruh Puisi Terhadap Kesehatan Emosional : Sebuah Tinjauan Pustaka: The Influence of Poetry on Emotional Health: A Literature Review - N.A, Septia Rizqi; Al Jamiliyati, Nasikhatul Ulla; Shafa, Sevi Ika Ariana; Yasmin, Aisyah; Maulida, Triska Amanda; Syafina, Velantika Puja Dwi Nara; Setyawati, Zahwa Alifia Aura Syfa (KIRANA : Social Science Journal, 2025)
This study investigated the impact of poetry on mental health, focusing on how writing and reading poetry can help manage stress, depression and anxiety. Through a literary and experimental approach, poetry therapy has been shown to relieve emotional tension, increase self-esteem, and encourage deep introspection. Poetry as a creative therapeutic tool not only supports the emotional recovery process but also builds mental balance. Research findings show the potential of poetry as an effective therapy for improving emotional well-being in a variety of therapeutic and personal settings. This research investigates the impact of poetry on mental health, with the aim of understanding the mechanisms by which poetry functions as a therapeutic tool. Through a literary and experimental approach, poetry is proven to reduce stress, anxiety, and depression by encouraging self-expression and deep emotional introspection. Writing or reading poetry can help you articulate difficult emotions, support the emotional healing process, and improve your mental well-being. This research also shows that poetry therapy is effective in improving self-esteem and emotional stability in many people.